Membaca Perempuan Dalam Kumpulan Cerpen Perempuan yang Menunggu Karya Dorothea Rosa Herliany - Laura Andri Retno M (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Positioning yourself as a woman by feeling all her existence and helplessness will make us able to read the text in a literary work of women. Literary works which written by female authors usually present messages and ideas contrary to the patriarchal system. If the reader simply places himself as a "reader" then he will not be able to capture the message and the idea. Instead they only concerned with the public's understanding and perception in general which is still dominated by patriarchal culture. Through the feminist’s approach "read as a woman" in the essay collection Perempuan yang Menunggu (The Waiting Women) by Dorothea Rosa's, "women readers" will find concrete images of the condition of women in accordance with reality. They will read, interpret and understand the body of women as well as their own body and identity. Ultimately, women are able to free themselves from the frame constraints that limit their creativity and overhaul the existing patriarchal systems